2010
DOI: 10.1007/s00542-010-1046-4
|View full text |Cite
|
Sign up to set email alerts
|

Power sensitivity of vibration energy harvester

Abstract: This paper deals with a power sensitivity improvement of an electromagnetic vibration energy harvester which generates electrical energy from ambient vibrations. The harvester provides an autonomous source of energy for wireless applications, with an expected power consumption of several mW, placed in environment excited by ambient mechanical vibrations. An appropriately tuned up design of the harvester with adequate sensitivity provides sufficient generating of electrical energy for some wireless applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…Detailed studies of the mechanical damping have not been found in literature, and the impact and suitability of different designs cannot be compared. The comparison of the harvester designs suggests that the dominant damping phenomena are material damping, in special cases friction [41] and possibly laminar viscid damping.…”
Section: Implications On Designmentioning
confidence: 99%
“…Detailed studies of the mechanical damping have not been found in literature, and the impact and suitability of different designs cannot be compared. The comparison of the harvester designs suggests that the dominant damping phenomena are material damping, in special cases friction [41] and possibly laminar viscid damping.…”
Section: Implications On Designmentioning
confidence: 99%
“…The design is based on a unique spring-less resonance mechanism [1], which provides a suitable sensitivity of the used energy harvesting application. The design is shown in Figure 2, where the moving mass is designed as a pendulum with the magnetic circuit is on the pendulum end.…”
Section: State Of the Art -Energy Harvesting From Mechanical Energymentioning
confidence: 99%
“…Measured characteristics for different vibration levels are presented in paper [1] and a review of harvested energy is shown in Table 1. The harvester was excited by the resonance frequency of vibrations.…”
Section: State Of the Art -Energy Harvesting From Mechanical Energymentioning
confidence: 99%
“…Multiple harvesters are arrayed to increase output voltages by summing up voltage from each harvester, or to increase bandwidth by differing from each harvester's natural frequency [6,7]. Recent studies reported advanced energyconversion mechanisms including the frequency up-conversion [3,6,8] and hybrid mechanisms [9,10]. In addition, new magnetic materials developed by micro-/nano-technologies are actively investigated [11].…”
Section: Introductionmentioning
confidence: 99%